Crop diversification: an important way-out for doubling farmers' income - Khanam, Rubina; Bhaduri, Debarati; Nayak, A. K. (Indian Farming, 2018)
Persistent low level of farmers’income can cause serious adverseeffect on the future of agriculture inthe country. To secure future ofagriculture and to improve livelihoodof half of India’s population,adequate attention needs to be givento improve the welfare of farmers andraise agricultural income.Introduction, adaption andacceptance of new varieties as well asnew and upcoming productiontechnologies can potentiallystrengthen farmers’ cropping systemsby increasing yields, improvingdrought resilience, boostingresistance to pests and diseases andalso by capturing new marketopportunities. There is a need toidentify crops and varieties that maysuit to a range of environments andfarmers’ preferences. Cropdiversification provides betterconditions for food security andenables farmers to grow surplusproducts for sale at market and thushelp to obtain increased income tomeet other needs related tohousehold well-being. Cropdiversification can enable farmers togain access to national andinternational markets with newproducts, food and medicinal plants.Diversifying from the monoculture oftraditional staples can have importantnutritional benefits for farmers indeveloping countries and can supporta country for becoming more selfreliantin terms of food production.Diversification can also manage pricerisk, on the assumption that not allproducts will suffer low market pricesat the same time and increase theprofitability of the farmingcommunity.